The Adjacency Pairs Analysis of Teacher Students Talks in Hearing Impairment Classroom - Nahar Nurun Nafi'; Desika Rinanda; Sularti Sularti (Register Journal, 2019)
ABSTRACT The purpose of this study is to investigate the components of adjacency pairs which appear in a conversation between an English teacher and hearing-impairment students in a special need classroom. Another aim is to find the dominance of English teacher in the special need classroom. Data are collected from a classroom observation, recording and transcribing their conversation during the teaching and learning activities in English classroom. Meanwhile, data analysis is carried out by identifying, analyzing and classifying based on Mc Charty’s theory of adjacency pairs., It is then found that there are 9 kinds of adjacency pairs committed from the interaction between English teachers and the hearing-impairment students as follows: (1) Compliment / Acceptance, (2) Information / Acknowledgement, (3) Greeting / Greeting, (4) Invitation / Acceptance, (5) Offer / Refusal, (6) Question / Answer, (7) Summons / Answer, (8) Accusation / Denial, (9) Offer / Acceptance. This study reveals a fact that various adjacency pairs occur in the special need classroom even though the teacher’s role is also quite powerful in the special need classroom. The finding of this study may become the reference for the teachers and practitioners who need deep understand toward characteristics of the special needs students especially for the impairment students.  Keywords: Adjacency Pairs, Teaching and Learning, Hearing-impairment Students